Voices. - Newmiller, William (WLA (1949-9752), 2006)
The essay presents the memories of the author's experiences in the Vietnam War. Common images of the war are presented along with the author's contrasting memories of being stationed in Wichita Falls, Texas, as a flight instructor. The essay provides a particular account with a training exercise with a Vietnamese student pilot.